2012
DOI: 10.3109/15622975.2011.650204
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease and type 2 diabetes: Two diseases, one common link?

Abstract: OBJECTIVES: Although Alzheimer's disease (AD) is the most common form of dementia in the elderly, its aetiology remains mostly unknown. A potential pathophysiological mechanism for AD arises from the knowledge that insulin is also synthesized independently in the central nervous system and is involved in the regulation of memory formation. AD may represent a brain-specific form of insulin resistance. METHODS: We used immunohistochemistry to investigate the numbers of cells expressing insulin receptor -subunit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Once active, AKT enters the cytoplasm where it leads to the phosphorylation and inactivation of GSK3 (Jolivalt et al, 2008 Consistent with the actual finding reported here, our group could already report that in AD patient less INSR were found especially in the hippocampal region of the brain (Bartl et al, 2012). Not only an impairment of INSR leads to an activation of GSK3β as explained before, also oxidative stress can enhance the activity of this kinase (Hernandez and Avila, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…Once active, AKT enters the cytoplasm where it leads to the phosphorylation and inactivation of GSK3 (Jolivalt et al, 2008 Consistent with the actual finding reported here, our group could already report that in AD patient less INSR were found especially in the hippocampal region of the brain (Bartl et al, 2012). Not only an impairment of INSR leads to an activation of GSK3β as explained before, also oxidative stress can enhance the activity of this kinase (Hernandez and Avila, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…These pathways involve glycogen synthase-kinase-3 (GSK3) inhibition, via protein kinase B (Akt/PKB) [ 16 , 17 ]. In addition, IR influences the accumulation/degradation of amyloid-β and tau protein, the major neuropathological hallmarks of the memory loss developed in Alzheimer’s disease (AD) [ 13 15 ]. We aimed to investigate whether cognitively impaired SHRs develop a central insulin resistance in parallel to the peripheral one, but data published so far on cognitive performance in the SHR model have indicated that measurements were done using different cognitive tests, comparing different control strains, using animals of different ages and not always done using both sexes [ 3 , 18 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glucose metabolic disorders are probably an initiating factor 1,2. A variety of mechanisms have been postulated in the risk of AD and diabetes mellitus (DM) 3,4. Some scholars have even proposed that AD is type 3 diabetes 5,6.…”
Section: Introductionmentioning
confidence: 99%